Preventing Hypothermia during Cesarean Birth: An Integrative Review. Issue 2 (March 2020) - Dendis, Michelle; Hooven, Katie
Abstract: Purpose: The purpose of this integrative review was to assess common warming measures used for prevention of hypothermia during the perioperative period for women having cesarean birth and to determine their efficacy. Methods: A literature search was conducted via electronic databases EBSCO, PUBMED, Academic Search Premier, Google Scholar, and CINAHL using keyword search terms hypothermia, cesarean, and warming . Inclusion criteria were articles written in English and published between 2006 and 2018. Results: Seventeen articles were included in the review, covering three common warming measures; intravenous (IV) fluid warming, forced-air warming, and combined IV fluid and forced-air warming. Several other warming modalities were noted including warming mattresses and various combinations of interventions. Clinical Implications: Maternal hypothermia risk is increased during the perioperative period for women having cesarean birth without use of warming measures. Warming modalities that are beneficial in preventing maternal hypothermia in women having cesarean birth are IV fluid warming, upper body force-air warming, ambient OR temperature, and warming mattresses. National standards and guidelines from the American Society of PeriAnesthesia Nurses, the Association of Perioperative Registered Nurses, and the Association of Women's Health, Obstetric, and Neonatal Nurses are consistent with current evidence and should be in place and followed in every maternity unit caring for women having cesarean birth. Abstract : In this integrative review, warming measures to prevent maternal hypothermia during the perioperative period for women having cesarean birth were evaluated. Warming measures found to be beneficial are intravenous fluid warming, upper body force-air warming, ambient operating room temperature, and warming mattresses. National guidelines from the American Society of PeriAnesthesia Nurses, the Association of Perioperative Registered Nurses, and the Association of Women's Health, Obstetric and Neonatal Nurses are consistent with current evidence and should be in place and followed in every maternity unit caring for women having cesarean birth.